2023
DOI: 10.31851/jmksp.v8i1.10941
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Islamic Education Institutions in Indonesia

Abstract: Intriguing changes have been made to the evolution of Islamic education in Indonesia. The phase evolutions were chronologically studied in this article. Prior to independence, then through the Old Order regime, New Order regime, and reform eras. This is library research. This library research found Each period has had a unique and significantly influenced the development of Islamic education in Indonesia in terms of systems, management, and methodology, all the way up to the way Islamic education is envisioned. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When the reform movement took place in 1998, many educators and founders of Nurul Fikri were involved in the establishment of the Justice Party, in line with the party's political declaration. This perspective illustrates the significant role of the Tarbiyah movement in Indonesia in political development, initially as a preaching movement, then branching out into education and political practice (Defnaldi, Yunani, Warisno, Andari, & Anshori, 2023). Therefore, it is not surprising that SIT is often regarded as an educational institution with political undertones, as it was founded by some political activists from the Justice Party.…”
Section: The Process Of Modernizing Islamic Educational Institutions Inmentioning
confidence: 92%
“…When the reform movement took place in 1998, many educators and founders of Nurul Fikri were involved in the establishment of the Justice Party, in line with the party's political declaration. This perspective illustrates the significant role of the Tarbiyah movement in Indonesia in political development, initially as a preaching movement, then branching out into education and political practice (Defnaldi, Yunani, Warisno, Andari, & Anshori, 2023). Therefore, it is not surprising that SIT is often regarded as an educational institution with political undertones, as it was founded by some political activists from the Justice Party.…”
Section: The Process Of Modernizing Islamic Educational Institutions Inmentioning
confidence: 92%
“…This potential strength is also due to the fact that Islamic educational institutions grow and develop from communities founded on strong intentions, sacred religious missions, the spirit of struggle with nationalist insights, and high nationalistic spirit. They see that from strong Islamic educational institutions will emerge respected community figures, figures of struggle, and dignified national figures (Defnaldi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Pesantren has moved forward by making updates in various aspects. Previous research by (Defnaldi et al, 2023) found that each period was unique and significantly influenced the development of Islamic education in Indonesia in terms of systems, management, and methodology, down to how Islamic education was envisioned.…”
Section: Introductionmentioning
confidence: 99%